Receptivity to the production of product service systems in the UK construction and manufacturing sectors: A comparative analysis - Cook, M.; Gottberg, Annika; Angus, Andrew; Longhurst, Philip J. (Elsevier Science B.V., Amsterdam., 2012)
Trajectories of service innovations emanating from manufacturing sectors have been of particular interest to those wishing to improve resource productivity and promote sustainable development. Research has focused on product service systems (PSSs), which are a category of service innovations deliberately designed to offer superior environmental performance. This paper draws on research which explored whether trajectories of PSS can be induced on new UK housing developments to satisfy household demand and prevent household waste. The research was undertaken with a UK speculative house-builder and facilities management service providers from its supplier network. Qualitative data were collected via interviews and focus groups to enable rich accounts of the range of factors in these firms' selection environments which affect receptivity to PSS production to be developed. These were compared with factors affecting receptivity to PSS production identified in a study of UK manufacturers. The results show that in contrast to the manufacturing study, clear drivers for PSS delivery on new housing developments are absent in external selection environments of participating firms and uncertainty associated with the potential of PSS concepts to satisfy household demand inhibits development of requisite competence for PSS delivery within these. Thus further research is needed to explore new PSS supply arrangements involving a range of household service providers.